Central Works of Philosophy Volume 4: The Twentieth Century: Moore to Popper - Shand, John (Central Works of Philosophy, 2006)
Central Works of Philosophy is a major multi-volume collection of essays on the core texts of the Western philosophical tradition. From Plato's "Republic" to the present day, the five volumes range over 2,500 years of philosophical writing covering the best, most representative, and most influential work of some of our greatest philosophers. Each essay has been specially commissioned and provides an overview of the work, clear and authoritative exposition of its central ideas, and an assessment of the work's importance. Together these books provide an unrivaled companion for studying and reading philosophy, one that introduces the reader to the masterpieces of the western philosophical canon. The period, 1900-60, which this volume covers, witnessed changes in logical and linguistic analysis far beyond anything dreamt of in the previous history of the subject. The volume begins with chapters on the key texts of the Cambridge philosophers, Moore, Russell and Wittgenstein, which together marked the emergence of analytical philosophy. The Vienna Circle of the 1920s, and the development of logical positivism in the 1930s and 1940s are represented by chapters on two fundamental works by Carnap and Ayer. William James' "Pragmatism," which formulated pragmatism's epistemology and made it known throughout the world represents in the volume the distinctive ideas of the American pragmatists. Essays on Husserl's "The Idea of Phenomenology," Heidegger's "Being and Time," Sartre's "Being and Nothingness" and Merleau-Ponty's "Phenomenology of Perception" cover the core texts of the hugely significant phenomenological movement. Of the linguistic philosophy that dominated the English-speaking world in the immediate postwar years, Wittgenstein's "Philosophical Investigations" and Ryle's "The Concept of the Mind" are discussed in turn. The volume concludes with Karl Popper's influential account of the nature of science. Volume 4 covers the key works of philosophy written in the peri